Sifat Fisik, Kimia, dan Organoleptik Telur Asin Melalui Penggaraman dengan Tekanan dan Konsentrasi Garam yang Berbeda - Rukmiasih, Rukmiasih; Ulupi, N.; Indriani, W. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Duck eggsplay a role inmaking salted eggs. This is becausethe duck eggshavea higherfat contentandlowerwater contentthanthose from chicken eggs or another poultry eggs.However, saltiness and grittiness level of salted eggs that were prefered byconsumers are still unknown. So the aim of this study was to evaluate the physical, chemiccal and organoleptic characteristics of salted eggs by salting with pressure level and salt concentration different.180 fresh duck eggswere used. This research used factorial pattern of complete randomize design 3x2. As treatments were pressure levels (0 bar, 1.5 bar, and 3 bar) and salt concentrations (20% and 25%).The parameters that observed included physical characteristic (grittiness level of salted egg yolk), chemical characteristics (contents of water and NaClin eggwhite and yolk), and organoleptic characteristics (general appearance, saltiness and grittiness of salted eggs). Data of physical and chemical characteristics were descriptivelly analyzed, while data of organoleptic characteristics were non-parametric statistically analyzed. The high level of pressure and the salt concentration that used in salting eggs produced salted eggs with the value of grittiness and NaCl content were high, but the value of water content was low. Combination of treatment without pressure (0 bar) with 20% and 25% salt concentrations, and on 1.5 bar pressure level with 20% salt concentration produced the salted egg that more prefered by panelists.